Habilidades auditivas e de linguagem em um grupo de crianças deficientes auditivas com diagnóstico e intervenção precoce - Brasil, Hélen Kopper (2011)
The early diagnosis and, consequently, the immediate amplification, as well as the therapeutical intervention and the family involvement, are indicators of success for the language development and for the hearing skills of children with hearing loss. Objective: To investigate the development of hearing and language capabilities of a group ofl children with congenital hearing. Methodology: This is a quantitative and qualitative research. It includes ten children with hearing loss, divided in two groups: with early and late diagnosis. All children were submitted to speech and hearing therapy and use hering aind or cochlear implant. All participants have speech perception and hearing with the electronic devices in the levels, suggested by Ling (1979) Results: time of use of hearing devices, the family involvement and amount of hearing experience showed good correlation with language development. When both groups were compared to each other, according to age at diagnosis, the language development and hearing skills, showed no statistical significance. Conclusion: The amount of hours which the child uses the hearing devices the family involvement, and amount of hearing experience are aspects that can influence the prognosis of children with hearing loss. The age of intervention did not show statistical significance between the two groups; concerning to hearing and language skills o for the children in this research